A pan-theoretical conceptualization of client involvement in psychotherapy. (2nd January 2016) - Morris, Eric; Fitzpatrick, Marilyn R.; Renaud, Jesse
Abstract: Objective: The present paper attempts to differentiate client involvement from other, similar process variables and presents a pan-theoretical conceptualization of client involvement.Method: A modified Delphi poll was conducted with 20 experienced clinicians and researchers. In two rounds of data collection, the experts completed a questionnaire designed to elicit their feedback on whether a variety of involvement items were representative of our pan-theoretical definition of client involvement.Results: The results of the survey provide insight into which types of client activities are good representations of client involvement.Conclusion: We propose that client involvement can be understood as being comprised of behavioral, cognitive, and emotional elements, and we provide concrete examples of these activities.